Composite material and preparation method thereof, positive pole piece, battery monomer, battery and electric device
By using a composite material containing lithium compounds, catalysts and carbon materials in the battery unit, the problem of the battery monomer's capacity is affected by lithium ion consumption, and the battery capacity is improved and the stability of the conductive network is achieved.
Patent Information
- Application Number
- CN202310910441.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-24
AI Technical Summary
During the first charging and discharging process of the battery cell, the formation of the solid electrolyte phase interface SEI film consumes a large amount of lithium ions, affecting the battery capacity.
A composite material contains lithium compounds, catalysts and carbon materials. Carbon materials have a hollow pipe structure. Lithium compounds and catalysts are set in the tubular structure to increase the battery capacity.
By using this composite material in the battery, lithium ions can be effectively supplemented, the capacity of the battery monomer can be increased, and the risk of conductive networks of the positive pole sheet can be reduced.
Smart Images

Figure CN119361616A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a composite material and a preparation method thereof, a positive electrode sheet, a battery cell, a battery and an electrical device. Background Art
[0002] As environmental pollution becomes increasingly serious, the new energy industry has attracted more and more attention. In the new energy industry, battery technology is an important factor related to its development.
[0003] The development of battery technology needs to consider many design factors, such as capacity, energy density, cycle life, reliability, etc. During the first charge and discharge process of a battery cell, a solid electrolyte interface SEI film will be produced on the surface of the negative electrode. The presence of the SEI film will consume a large amount of lithium ions and affect the capacity of the battery cell. Therefore, how to provide a composite material to supplement lithium ions and thus increase the capacity of the battery cell is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its object is to provide a composite material to improve the capacity of a battery cell.
[0005] In order to achieve the above-mentioned objectives, the present application provides a composite material and a preparation method thereof, a positive electrode sheet, a battery cell, a battery and an electrical device.
[0006] In a first aspect, a composite material is provided, comprising: a lithium-containing compound, a catalyst and a carbon material, wherein the carbon material has a hollow tubular structure, and the lithium-containing compound and the catalyst are arranged in the tubular structure; the lithium-containing compound comprises lithium, carbon and oxygen; and the catalyst comprises at least one of an oxide of a transition metal, a carbide of a transition metal or a nitride of a transition metal.
[0007] In the embodiment of the present application, the lithium-containing compound can decompose to produce lithium ions and gas, thereby replenishing lithium ions to the battery; the catalyst can catalyze the decomposition of the lithium-containing compound; the carbon material has a hollow tubular structure, and the lithium-containing compound and the catalyst are located in the tubular structure, which is conducive to increasing the capacity of the battery. Therefore, the technical solution of the embodiment of the present application can increase the capacity of the battery cell.
[0008] In a possible implementation, the lithium-containing compound and the catalyst are disposed on the inner wall of the tubular structure. In this way, the lithium-containing compound and the catalyst can be better disposed in the tubular structure, thereby reducing the risk of the lithium-containing compound and the catalyst detaching from the tubular structure when the composite material is short.
[0009] In a possible implementation, at least part of the catalyst is located on the surface of the lithium-containing compound, which is conducive to the catalyst catalyzing the decomposition of the lithium-containing compound.
[0010] In one possible implementation, the chemical formula of the lithium-containing compound is Li2C x O y , wherein 1≤x≤4, 3≤y≤6. Optionally, the lithium-containing compound includes at least one of: Li2C2O4, Li2CO3, Li2C4O4, Li2C3O5 or Li2C4O6. The above-mentioned lithium-containing compound can be decomposed into lithium ions and gas (such as carbon monoxide, carbon dioxide) under the action of voltage and catalyst. The lithium ions produced by the decomposition can play a role in replenishing lithium ions, which is beneficial to improving the capacity of the battery; the gas produced by the decomposition will not remain in the positive electrode sheet, and the long-term reliability and other performance of the battery cell will not be affected by the residues produced by the decomposition. In addition, the above-mentioned lithium-containing compound has good stability, can exist stably in air and organic solvents, and is compatible with the coating process of the positive electrode slurry.
[0011] In a possible implementation, the chemical formula of the transition metal oxide is M α O β , wherein 0<α≤3, 0<β≤5, M includes at least one of Ni, Co, Fe, Mn, V, Cr, Cu or Ti; optionally, M α O β The catalyst comprises at least one of NiO, Co3O4, Fe2O3, MoO3 or V2O5. The catalyst can reduce the decomposition voltage of the lithium-containing compound, so that the lithium-containing compound can be decomposed at a lower voltage.
[0012] In a possible implementation, the transition metal carbide includes at least one of molybdenum carbide, vanadium carbide, tungsten carbide, titanium carbide, cobalt carbide, iron carbide or nickel carbide; and / or the transition metal nitride includes at least one of molybdenum nitride, vanadium nitride, titanium nitride, manganese nitride, cobalt nitride, iron nitride or nickel nitride. The above transition metal carbides and transition metal nitrides have good catalytic effects and can catalyze the decomposition of lithium-containing compounds.
[0013] In a possible implementation, based on the total mass of the composite material, the mass content A of the carbon material satisfies: 1wt%≤A≤40wt%; optionally, A satisfies: 2wt%≤A≤25wt%.
[0014] When the mass content A of the carbon material is not less than 1wt%, the carbon material can completely wrap the catalyst and the lithium-containing compound, and the conductivity of the composite material is relatively high, which is beneficial to improving the capacity of the battery cell; when the mass content A of the carbon material does not exceed 40wt%, the carbon material has a suitable mass ratio, and the catalyst and the lithium-containing compound also have a suitable mass ratio, which is beneficial to improving the capacity of the battery cell.
[0015] In a possible implementation, based on the total mass of the composite material, the mass content B of the catalyst satisfies: 0.1wt%≤B≤20wt%; optionally, B satisfies: 0.5wt%≤B≤10wt%.
[0016] When the mass content B of the catalyst is not less than 0.1wt%, the contact area between the catalyst and the lithium-containing compound is appropriate, the catalyst has a good catalytic effect, is beneficial to catalyze the decomposition of the lithium-containing compound, and is beneficial to improving the capacity of the battery cell; when the mass content B of the catalyst does not exceed 20wt%, it is beneficial to add more lithium-containing compounds to the composite material, which is beneficial to improving the capacity of the battery cell.
[0017] In a possible implementation, based on the total mass of the composite material, the mass content C of the lithium-containing compound satisfies: 45wt%≤B≤98.9wt%; optionally, C satisfies: 70wt%≤B≤85wt%.
[0018] When the mass content C of the lithium-containing compound is not less than 45wt%, the content of the lithium-containing compound is relatively high, and can be decomposed to produce more lithium ions, thereby replenishing more lithium ions to the negative electrode, which is beneficial to increasing the capacity of the battery cell; when the mass content C of the lithium-containing compound does not exceed 98.9wt%, the carbon material and the catalyst in the composite material have a certain mass content, which is beneficial to taking into account the decomposition voltage of the lithium-containing compound, the conductivity of the composite material, and the number of lithium ions decomposed from the lithium-containing compound, thereby obtaining a higher battery capacity.
[0019] In a possible implementation, the aspect ratio E of the carbon material satisfies: 100:1≤E≤3000:1; optionally, E satisfies: 200:1≤E≤2000:1.
[0020] When the aspect ratio E of the carbon material is not less than 100:1, the composite material has a good conductive effect; when the aspect ratio E of the carbon material does not exceed 3000:1, on the one hand, it is conducive to the synthesis of the carbon material, and on the other hand, it can reduce the risk of agglomeration of the carbon material, thereby reducing the risk of a small increase in the capacity of the battery cell due to agglomeration of the carbon material.
[0021] In a possible implementation, in the composite material, the decomposition voltage V1 of the lithium-containing compound satisfies: V1 < 4.8 V; optionally, V1 satisfies: V1 < 4.4 V. In this way, the lithium-containing compound can be decomposed at a lower voltage to replenish lithium to the negative electrode, which can reduce the risk of structural changes of the positive electrode active material caused by high voltage, and is conducive to improving the stability and cycle performance of the battery cell.
[0022] In a possible implementation, the resistivity P of the composite material satisfies: 0.2Ω·cm<P<101Ω·cm; optionally, P satisfies: 0.2Ω·cm<P<5.5Ω·cm. In this way, the composite material has a suitable resistivity, so that the positive electrode sheet has a suitable conductivity, and the battery cell has a relatively suitable capacity.
[0023] In a possible implementation, the average volume particle size Dv of the lithium-containing compound is 1 50 is greater than the average volume particle size Dv of the catalyst 2 50, so that the catalyst is attached to the surface of the lithium-containing compound, which is convenient for catalyzing the decomposition of the lithium-containing compound. Optionally, the average volume particle size Dv of the lithium-containing compound 1 50Satisfy: 100nm≤Dv 1 50≤1000nm, the average volume particle size Dv of the catalyst 2 50 satisfies: 50nm≤Dv 2 50≤500nm. In this way, it is beneficial to increase the specific surface area of the lithium-containing compound and the catalyst, and to increase the contact area between the lithium-containing compound and the catalyst, thereby improving the effect of the catalyst on the catalytic decomposition of the lithium-containing compound. In addition, since the catalytic effect of the catalyst is improved, the requirement for the mass proportion of the catalyst in the composite material is reduced. When the catalyst has a smaller mass content, the decomposition voltage of the lithium-containing compound can be reduced; and it is also beneficial to increase the mass content of the lithium-containing compound and the carbon material in the composite material, and improve the energy density of the battery cell.
[0024] In a possible implementation, the average volume particle size Dv of the lithium-containing compound is 1 50 and the average volume particle size Dv of the catalyst 2 The difference between 50 and 50 is 50 nm to 1000 nm. This is conducive to the adsorption of the catalyst on the surface of the lithium-containing compound, thereby catalyzing the decomposition of the lithium-containing compound.
[0025] In the second aspect, a method for preparing the composite material in the first aspect and any possible implementation thereof is provided, comprising: mixing a lithium-containing compound and a catalyst to obtain a mixed material of the lithium-containing compound and the catalyst, wherein the catalyst comprises at least one of an oxide of a transition metal, a carbide of a transition metal, or a nitride of a transition metal, and the lithium-containing compound comprises lithium, carbon, and oxygen; adding the mixed material of the lithium-containing compound and the catalyst to a slurry containing a polymer material to obtain an electrospinning stock solution; electrostatically spinning the electrospinning stock solution to obtain a precursor; and calcining the precursor in an inert atmosphere to obtain the composite material. By the above method, the composite material of the embodiment of the present application can be prepared, and the composite material is conducive to improving the capacity of the battery monomer.
[0026] In one possible implementation, the chemical formula of the lithium-containing compound is Li2C x O y , wherein 1≤x≤4, 3≤y≤6. Optionally, the lithium-containing compound comprises at least one of Li2C2O4, Li2CO3, Li2C4O4, Li2C3O5 or Li2C4O6.
[0027] In a possible implementation, the chemical formula of the transition metal oxide is M α O β , wherein 0<α≤3, 0<β≤5, M includes at least one of Ni, Co, Fe, Mn, V, Cr, Cu or Ti; optionally, M α O β Includes: at least one of NiO, Co3O4, Fe2O3, MoO3 or V2O5.
[0028] In one possible implementation, the carbide of the transition metal includes: at least one of molybdenum carbide, vanadium carbide, tungsten carbide, titanium carbide, cobalt carbide, iron carbide or nickel carbide; and / or, the nitride of the transition metal includes: at least one of molybdenum nitride, vanadium nitride, titanium nitride, manganese nitride, cobalt nitride, iron nitride or nickel nitride.
[0029] In a possible implementation, the solute in the slurry containing the polymer material includes the polymer material, and the solvent in the slurry containing the polymer material is an organic solvent; optionally, the organic solvent includes N,N-dimethylformamide. The polymer material has good solubility in the organic solvent, and after the polymer powder is added to the organic solvent, it is easy to prepare the above solution. N,N-dimethylformamide has good stability, so that the above slurry has good performance.
[0030] In a possible implementation, the mass ratio D of the polymer material to the N,N-dimethylformamide satisfies: 1:20≤D≤1:1; optionally, D satisfies: 1:10≤D≤1:5. When D is not less than 1:20, the polymer material and N,N-dimethylformamide have a suitable mass ratio, which facilitates the smooth progress of electrospinning and reduces the difficulty of electrospinning; when D does not exceed 1:1, the risk of a thin electrospinning solution caused by more N,N-dimethylformamide and less polymer material can be reduced, thereby reducing the risk of composite material fracture during subsequent calcination. By reasonably setting the size of D, the smooth progress of electrospinning and the preparation of composite materials are facilitated.
[0031] In a possible implementation, the polymer material includes: at least one of polyvinyl pyrrolidone, polyacrylonitrile or polyethylene oxide; optionally, the polymer material includes polyacrylonitrile.
[0032] In a possible implementation, the calcination temperature T satisfies: 300°C ≤ T ≤ 480°C; optionally, T satisfies: 350°C ≤ T ≤ 450°C. This is conducive to achieving sufficient carbonization of the polymer material and reducing the risk of thermal decomposition of the lithium-containing compound due to excessively high temperature, thereby facilitating the preparation of the carbon material with a hollow tubular structure in the composite material.
[0033] In a possible implementation, the mixing of the lithium-containing compound and the catalyst to obtain a mixed material of the lithium-containing compound and the catalyst comprises: mixing the lithium-containing compound and the catalyst and performing high-energy ball milling to obtain the mixed material of the lithium-containing compound and the catalyst. High-energy ball milling can obtain lithium-containing compounds and catalysts with smaller particle sizes, which is conducive to making the lithium-containing compound and the catalyst mix more uniformly, and is conducive to increasing the specific surface area of the lithium-containing compound and the catalyst, thereby facilitating improving the catalytic effect of the catalyst.
[0034] In a possible implementation, the ball-to-material ratio F of the high-energy ball mill satisfies: 10:1≤F≤15:1; and / or, the revolution speed R1 of the high-energy ball mill satisfies: 1000r / min≤R1≤1500r / min; and / or, the rotation speed R2 of the high-energy ball mill satisfies: 2500r / min≤R2≤3000r / min. In this way, the high-energy ball mill has suitable process parameters, which is convenient for obtaining lithium-containing compounds and catalysts with suitable particle sizes.
[0035] In a possible implementation, the mass ratio K of the lithium-containing compound to the catalyst satisfies: 15:1≤K≤40:1. In this way, the lithium-containing compound and the catalyst have a suitable mass ratio, and the lithium-containing compound can be more fully decomposed under the catalytic action of the catalyst, which is beneficial to improving the capacity of the battery cell.
[0036] In a possible implementation, the average volume particle size Dv of the lithium-containing compound is 1 50 is greater than the average volume particle size Dv of the catalyst 2 50; the average volume particle size Dv of the lithium-containing compound 1 50Satisfy: 100nm≤Dv 1 50≤1000nm, the average volume particle size Dv of the catalyst 2 50 satisfies: 50nm≤Dv 2 50≤500nm.
[0037] In a possible implementation, in the electrospinning, the voltage is 15 kV, the propulsion speed of the electrospinning stock solution is 0.2 mL / min, the receiving distance is 15 cm, and the spinning time is 12 h. In this way, the preparation of the composite material is facilitated by appropriate preparation process parameters.
[0038] In a third aspect, a positive electrode plate is provided, comprising a positive electrode active material; a composite material in the first aspect and any possible implementation thereof, and / or a composite material prepared by the method in the second aspect and any possible implementation thereof.
[0039] In a possible implementation, the resistance R of the positive electrode sheet satisfies: 0.3Ω<R<0.5Ω. In this way, the positive electrode sheet has appropriate conductivity and the battery cell has appropriate capacity.
[0040] In a fourth aspect, a battery cell is provided, comprising the positive electrode plate in the third aspect and any possible implementation thereof.
[0041] In a fifth aspect, a battery is provided, comprising the battery cell described in the fourth aspect.
[0042] In a sixth aspect, an electrical device is provided, comprising the battery described in the fifth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0044] Figure 1 A schematic diagram of a composite material according to an embodiment of the present application;
[0045] Figure 2 A schematic diagram of a method for preparing a composite material according to an embodiment of the present application;
[0046] Figure 3 A schematic diagram of a battery cell according to an embodiment of the present application;
[0047] Figure 4 A schematic diagram of a battery according to an embodiment of the present application;
[0048] Figure 5 FIG. 1 is a schematic diagram of an electrical device according to an embodiment of the present application. DETAILED DESCRIPTION
[0049] The detailed description of the composite material and its preparation method, positive electrode sheet, battery cell, battery, and electrical device of the present application is specifically disclosed with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0050] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0051] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0052] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0053] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0054] The development of battery technology needs to consider many design factors, such as capacity, energy density, cycle life, reliability, etc. During the first charge and discharge process of the battery cell, a solid electrolyte interface SEI film will be produced on the surface of the negative electrode. The presence of the SEI film will consume a large amount of lithium ions and affect the capacity of the battery cell. In order to increase the capacity of the battery cell, additives are added to the positive electrode slurry. The additives include Li2C2O4 and Ni x O, where 0.67≤x≤1. x Under the catalytic action of O, the Li2C2O4 in the additive can decompose to produce lithium ions under low voltage conditions, completing the lithium replenishment of the negative electrode, while also reducing the risk of irreversible structural changes in the positive electrode active material under high charging voltage conditions. However, after the decomposition of Li2C2O4, holes will be left at the original position of Li2C2O4, causing the conductive network of the positive electrode sheet to be destroyed, affecting the transmission of ions and electrons, and not conducive to improving the capacity of the battery cell. In addition, the conductivity of Li2C2O4 is poor, which is not conducive to improving the capacity of the battery cell.
[0055] In view of this, an embodiment of the present application provides a composite material. In the composite material, the lithium-containing compound and the catalyst are arranged in a carbon material tubular structure having a hollow tubular structure, so that the influence of the vacancies generated after the decomposition of the lithium-containing compound on the ion transmission performance and the electron transmission performance of the positive electrode plate can be reduced, and the arrangement of the carbon material is also conducive to improving the conductivity of the composite material. Therefore, the composite material of the embodiment of the present application can increase the capacity of the battery.
[0056] The composite material in the embodiment of the present application can be used as a lithium supplement, that is, it can supplement the lithium ions consumed by the negative electrode. As an example, the composite material can be mixed with the positive electrode active material to prepare a positive electrode slurry for use.
[0057] The battery cell in the embodiment of the present application can be used as a minimum unit of a battery. The battery cell includes a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte, and the like.
[0058] [Composite Materials]
[0059] Figure 1 FIG. 1 is a schematic diagram of a composite material according to an embodiment of the present application. Figure 1 As shown, the composite material 1 includes a lithium-containing compound 11 , a catalyst 12 and a carbon material 13 .
[0060] The carbon material 13 has a hollow tubular structure, and the lithium-containing compound 11 and the catalyst 12 are disposed in the tubular structure.
[0061] The lithium-containing compound 11 and the catalyst 12 may be disposed in the tubular structure without contacting the inner wall of the tubular structure, or may be disposed on the inner wall of the tubular structure.
[0062] The carbon material 13 is a carbon tube, for example, a nano-scale carbon tube. The carbon material 13 is in a fibrous shape, and the carbon material 13 can extend continuously in different directions.
[0063] The carbon material 13 may be an amorphous carbon material. In some embodiments, the carbon material 13 is a completely carbonized polymer material, that is, the carbon material 13 may only include carbon elements.
[0064] The lithium-containing compound 11 and the catalyst 12 are disposed in the tubular structure of the carbon material 13, which means that the lithium-containing compound 11 and the catalyst 12 are coated inside the carbon material 13, and the lithium-containing compound 11 and the catalyst 12 are not in direct contact with the outside world (such as the positive electrode active material).
[0065] Since the lithium-containing compound 11 is located in the tubular structure of the carbon material 13, after the lithium-containing compound 11 is decomposed, the holes or vacancies left at the original position of the lithium-containing compound 11 will not be directly reflected on the positive electrode sheet, so the risk of the conductive network of the positive electrode sheet being destroyed is reduced, and the impact on the transmission of electrons and ions in the positive electrode sheet is small, thereby improving the capacity of the battery cell. In addition, after the lithium-containing compound 11 is decomposed, vacancies or holes are left on the inner wall of the tubular structure of the carbon material 13, and the vacancies can enhance the infiltration of the electrolyte. The electrolyte on the vacancies can provide a channel for ion transmission, which is beneficial to the transmission of ions (such as lithium ions), thereby facilitating the improvement of the capacity of the battery.
[0066] The carbon material 13 has good electrical conductivity. By adding the carbon material 13 to the composite material 1, it is beneficial to reduce the resistivity of the composite material 1 and improve the capacity of the battery cell.
[0067] The lithium-containing compound 11 includes lithium, carbon and oxygen. The lithium-containing compound 11 may include an organic lithium-containing compound, such as Li2C2O4, or an inorganic lithium-containing compound, such as Li2CO3.
[0068] The lithium-containing compound 1 can be decomposed under the action of voltage to decompose into lithium ions and carbon oxides (such as CO, CO2). The lithium ions produced by the decomposition can supplement lithium ions to the negative electrode, thereby facilitating the improvement of the battery capacity.
[0069] The catalyst 12 includes at least one of an oxide of a transition metal, a carbide of a transition metal, or a nitride of a transition metal. The catalyst 12 can reduce the decomposition voltage of the lithium-containing compound 11.
[0070] The carbides and nitrides of transition metals can be obtained by treating the oxides of transition metals. The carbides of transition metals can be molybdenum carbide and tungsten carbide, and the nitrides of transition metals can be molybdenum nitride and manganese nitride.
[0071] Transition metal oxides, transition metal carbides, and transition metal nitrides not only have high conductivity, but also have abundant surface active sites and high specific surface area, which can catalyze the decomposition of lithium-containing compounds.
[0072] The oxides, carbides and nitrides of transition metals can catalyze the decomposition of the lithium-containing compound 11 under the action of voltage, that is, the decomposition voltage of the lithium-containing compound 11 can be reduced.
[0073] As an example, the catalyst is an oxide of a transition metal, such as Ni x O, wherein 0.67≤x≤1, embodiments of the present application include but are not limited to this, as long as it can catalyze the decomposition of lithium-containing compounds.
[0074] The composite material 1 is a fibrous material, and the composite material 1 and the carbon material 13 have the same shape.
[0075] In the embodiment of the present application, the lithium-containing compound 11 can decompose under the action of voltage to produce lithium ions and gas, thereby replenishing lithium ions to the battery; the catalyst 12 can catalyze the decomposition of the lithium-containing compound 11, so that the lithium-containing compound 11 decomposes at a lower voltage, so that the lithium-containing compound 11 can be adapted to a variety of positive electrode active materials; the carbon material 13 has a hollow tubular structure, and the lithium-containing compound 11 and the catalyst 12 are located in the tubular structure, so that after the decomposition of the lithium-containing compound 11, the risk of the vacancies left after the decomposition of the lithium-containing compound 11 to destroy the conductive network of the pole piece is reduced, and the pole piece has good ion transmission performance and electron transmission performance, which is conducive to improving the capacity of the battery cell; in addition, the vacancies left by the lithium-containing compound 11 in the tubular structure of the carbon material 13 also help to increase the wettability of the electrolyte, which is conducive to the transmission of ions, thereby further improving the capacity of the battery. Therefore, the technical solution of the embodiment of the present application can improve the capacity of the battery cell.
[0076] In some embodiments, the lithium-containing compound 11 and the catalyst 12 are disposed on the inner wall of the tubular structure. In this way, the lithium-containing compound and the catalyst can be better disposed in the tubular structure, thereby reducing the risk of the lithium-containing compound and the catalyst detaching from the tubular structure when the composite material is short.
[0077] In some embodiments, at least a portion of the catalyst 12 is located on the surface of the lithium-containing compound 11. In this way, the catalyst 12 located on the surface of the lithium-containing compound 11 can catalyze the decomposition of the lithium-containing compound 11 and reduce the decomposition voltage of the lithium-containing compound 11.
[0078] In the composite material 1 , part of the catalyst 12 may not be located on the surface of the lithium-containing compound 11 , but may be located in the tubular structure of the carbon material 13 ; or all of the catalyst 12 may be located on the surface of the lithium-containing compound 11 .
[0079] In some embodiments, the chemical formula of the lithium-containing compound 11 is Li2C x O y , where 1≤x≤4, 3≤y≤6.
[0080] For the chemical formula Li2C x O y For example, x and y satisfy the following relationship: x+y=2n, 2≤n≤5.
[0081] Wherein, x can be 1, 2, 3, 4 or any value within the above range, y can be 3, 4, 5, 6 or any value within the above range, and n can be 2, 3, 4, 5 or any value within the above range. As an example, x, y, and n are all positive integers.
[0082] The lithium-containing compound 11 can be decomposed into lithium ions and gas (such as carbon monoxide and carbon dioxide) under the action of voltage and catalyst 12. The lithium ions produced by decomposition can play a role in replenishing lithium ions, which is beneficial to improving the capacity of the battery; the gas produced by decomposition will not remain in the positive electrode sheet, and the long-term reliability and other performance of the battery cell will not be affected by the residue produced by decomposition. In addition, the lithium-containing compound 11 has good stability, can exist stably in air and organic solvents, and is compatible with the coating process of the positive electrode slurry.
[0083] As an example, the gas generated by the decomposition of the lithium-containing compound 11 can be sucked out of the battery cell through a tool such as a suction nozzle during the formation step.
[0084] In some embodiments, the lithium-containing compound 11 includes at least one of Li2C2O4, Li2CO3, Li2C4O4, Li2C3O5, or Li2C4O6. The above lithium-containing compounds are easy to obtain and can be easily applied to the composite material 1.
[0085] In some embodiments, the transition metal oxide has the formula M α O β , wherein 0<α≤3, 0<β≤5, and M includes at least one of Ni, Co, Fe, Mn, V, Cr, Cu or Ti.
[0086] α may be 0.5, 1, 2, 3 or any value within the above range, and β may be 0.5, 1, 2, 3, 4, 5 or any value within the above range. In some examples, α and β are positive integers.
[0087] The catalyst 12 can reduce the decomposition voltage of the lithium-containing compound 11, so that the lithium-containing compound 11 can be decomposed at a lower voltage.
[0088] In some embodiments, M α O β The catalyst comprises at least one of NiO, Co3O4, Fe2O3, MoO3 or V2O5. The catalyst is easy to obtain and can be applied to the composite material 1.
[0089] In some embodiments, the carbide of the transition metal includes at least one of molybdenum carbide, vanadium carbide, tungsten carbide, titanium carbide, cobalt carbide, iron carbide or nickel carbide; and / or, the nitride of the transition metal includes at least one of molybdenum nitride, vanadium nitride, titanium nitride, manganese nitride, cobalt nitride, iron nitride or nickel nitride. The above transition metal carbides and transition metal nitrides have good catalytic effects and can catalyze the decomposition of lithium-containing compounds.
[0090] In some embodiments, based on the total mass of the composite material 1 , the mass content A of the carbon material 13 satisfies: 1 wt % ≤ A ≤ 40 wt %.
[0091] A may be 1 wt%, 10 wt%, 15 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt% or any value within the above range.
[0092] When the mass content A of the carbon material 13 is not less than 1wt%, the carbon material 13 can completely wrap the catalyst 12 and the lithium-containing compound 11, and the conductivity of the composite material 1 is relatively high, which is beneficial to improving the capacity of the battery cell; when the mass content A of the carbon material 13 does not exceed 40wt%, the carbon material 13 has a suitable mass ratio, and the catalyst 12 and the lithium-containing compound 11 also have a suitable mass ratio, which is beneficial to improving the capacity of the battery cell.
[0093] In this embodiment, by setting A to satisfy 1 wt % ≤ A ≤ 40 wt %, the battery cell has a higher capacity.
[0094] In some embodiments, A satisfies: 2wt%≤A≤25wt%. In this way, the battery cell can have both high conductivity and high capacity.
[0095] In some embodiments, based on the total mass of the composite material 1 , the mass content B of the catalyst 12 satisfies: 0.1 wt %≤B≤20 wt %.
[0096] B may be 0.1 wt%, 0.5 wt%, 1 wt%, 5 wt%, 8 wt%, 10 wt%, 15 wt%, 20 wt% or any value within the above range.
[0097] When the mass content B of the catalyst 12 is not less than 0.1wt%, the contact area between the catalyst 12 and the lithium-containing compound 11 is appropriate, and the catalyst 12 has a good catalytic effect, which is beneficial to catalyze the decomposition of the lithium-containing compound 11 and to improve the capacity of the battery cell; when the mass content B of the catalyst 12 does not exceed 20wt%, it is beneficial to add more lithium-containing compounds 11 to the composite material 1, which is beneficial to improve the capacity of the battery cell.
[0098] In some embodiments, B satisfies: 0.5 wt % ≤ B ≤ 10 wt %. This is beneficial for taking into account both the capacity of the battery cell and the decomposition voltage of the lithium-containing compound 11 .
[0099] In some embodiments, based on the total mass of the composite material 1 , the mass content C of the lithium-containing compound 11 satisfies: 45 wt % ≤ B ≤ 98.9 wt %; alternatively, C satisfies: 70 wt % ≤ B ≤ 85 wt %.
[0100] When the mass content C of the lithium-containing compound 11 is not less than 45wt%, the content of the lithium-containing compound 11 is relatively high, and can be decomposed to produce more lithium ions, thereby replenishing more lithium ions to the negative electrode, which is beneficial to increasing the capacity of the battery cell; when the mass content C of the lithium-containing compound 11 does not exceed 98.9wt%, the carbon material 13 and the catalyst 12 in the composite material have a certain mass content, which is beneficial to taking into account the decomposition voltage of the lithium-containing compound 11, the conductivity of the composite material 1, and the number of lithium ions decomposed by the lithium-containing compound 11, thereby obtaining a higher battery capacity.
[0101] In some embodiments, the aspect ratio E of the carbon material 13 satisfies: 100:1≤E≤3000:1.
[0102] E can be 100:1, 200:1, 500:1, 1000:1, 1500:1, 2000:1, 3000:1 or any value within the above range.
[0103] The aspect ratio is common knowledge in the art, has a well-known meaning in the art, and can be measured by a well-known test method and instrument in the art. The aspect ratio may refer to the ratio of the length to the diameter of the carbon material 13. Specifically, it is the ratio of the length to the outer diameter of the tubular structure of the carbon material 13.
[0104] When the aspect ratio E of the carbon material 13 is not less than 100:1, the composite material 1 has a good conductive effect; when the aspect ratio E of the carbon material 13 does not exceed 3000:1, on the one hand, it is beneficial to the synthesis of the carbon material 13, and on the other hand, it can reduce the risk of agglomeration of the carbon material 13, thereby reducing the risk of a small increase in the capacity of the battery cell due to agglomeration of the carbon material 13.
[0105] In some embodiments, E satisfies: 200:1≤E≤2000:1. In this way, the battery cell has a higher capacity.
[0106] In some embodiments, in the composite material 1 , the decomposition voltage V1 of the lithium-containing compound 11 satisfies: V1<4.8V; alternatively, V1 satisfies: V1<4.4V. For example, V1 is 4.79V, 4.4V, 4.3V, etc.
[0107] The decomposition voltage of the lithium-containing compound 11 is common knowledge in the art, has a meaning known in the art, and can be measured by testing methods and instruments known in the art.
[0108] The lithium-containing compound 11 can be decomposed at a lower voltage to replenish lithium to the negative electrode, which can reduce the risk of structural changes in the positive electrode active material caused by high voltage, and is beneficial to improving the stability and cycle performance of the battery cell.
[0109] In some embodiments, the resistivity P of the composite material 1 satisfies: 0.2Ω·cm<P<5.5Ω·cm. For example, P is 0.23Ω·cm, 1Ω·cm, 5.49Ω·cm or any value within the above range.
[0110] Resistivity is common knowledge in the art, has a meaning commonly known in the art, and can be measured by testing methods and instruments commonly known in the art.
[0111] The resistivity in the examples of the present application is the resistivity measured after the composite material is pressed into a sheet at a pressure of 20 MPa. Generally speaking, the greater the pressure, the lower the resistivity.
[0112] The composite material 1 has a suitable resistivity, so that the positive electrode sheet has a suitable conductivity and the battery cell has a relatively suitable capacity.
[0113] In some embodiments, the average volume particle size Dv of the lithium-containing compound 11 is 150 is greater than the average volume particle size Dv of catalyst 12 2 50. In this way, the catalyst 12 is advantageously attached to the surface of the lithium-containing compound 11, thereby facilitating the catalytic effect of the catalyst 12.
[0114] The average volume particle size is common knowledge in the art, has a meaning commonly known in the art, and can be measured by testing methods and instruments commonly known in the art.
[0115] In some embodiments, the average volume particle size Dv of the lithium-containing compound 11 is 1 50 and the average volume particle size Dv of catalyst 12 2 The difference between Dv and 50 is 50nm to 1000nm. 1 50 is 100nm, Dv 2 50 is 50nm; Dv 1 50 is 500nm, Dv 2 50 is 200nm; or Dv 1 50 is 1000nm, Dv 2 50 is 500nm. Dv 1 50 and Dv 2 The difference of 50 is 50 nm, 100 nm, 500 nm, 1000 nm or any value within the above range. In this way, the catalyst 12 is advantageously adsorbed on the surface of the lithium-containing compound 11, thereby catalyzing the decomposition of the lithium-containing compound 11.
[0116] In some embodiments, the average volume particle size Dv of the lithium-containing compound 11 is 1 50Satisfy: 100nm≤Dv 1 50≤1000nm, average volume particle size Dv of catalyst 12 2 50 satisfies: 50nm≤Dv 2 50≤500nm.
[0117] In this way, it is beneficial to increase the specific surface area of the lithium-containing compound 11 and the catalyst 12, and it is beneficial to increase the contact area between the lithium-containing compound 11 and the catalyst 12, so as to improve the effect of the catalyst 12 on the catalytic decomposition of the lithium-containing compound 11. In addition, since the catalytic effect of the catalyst 12 is improved, the requirement for the mass proportion of the catalyst 12 in the composite material 1 is reduced. When the catalyst 12 has a smaller mass content, the decomposition voltage of the lithium-containing compound 11 can be reduced; and it is also beneficial to increase the mass content of the lithium-containing compound 11 and the carbon material 13 in the composite material 1, and improve the energy density of the battery cell.
[0118] Combination of the above Figure 1 The product side of the composite material of the embodiment of the present application is described below. Figure 2 The content on the preparation method side of the composite material is described, wherein similar content can refer to the description on the product side of the composite material, and will not be repeated here.
[0119] [Method for preparing composite material]
[0120] Figure 2 FIG. 1 is a schematic diagram of a method for preparing a composite material according to an embodiment of the present application. The method can be used to prepare the composite material in any of the above embodiments. Figure 2 As shown, the method 200 includes the following steps.
[0121] Step 210, mixing the lithium-containing compound 11 and the catalyst 12 to obtain a mixed material of the lithium-containing compound 11 and the catalyst 12. The catalyst 12 includes at least one of a transition metal oxide, a transition metal carbide or a transition metal nitride, and the lithium-containing compound 11 includes lithium, carbon and oxygen.
[0122] Step 220: Add the mixed material of the lithium-containing compound and the catalyst into the slurry containing the polymer material to obtain an electrospinning stock solution.
[0123] For example, a polymer material is added to an organic solvent, heated and stirred until the polymer material is dissolved to obtain a slurry containing the polymer material; then, a mixed material containing a lithium compound 11 and a catalyst 12 is added to the slurry to obtain an electrospinning stock solution.
[0124] As an example, a polymer material is added to an N,N-dimethylformamide (DMF) solution, heated and continuously stirred for a period of time. The heating temperature during stirring is 80° C., the heating time is 10 hours, and the stirring speed is 1000 rpm. After the polymer material is completely dissolved, the mixed material containing the lithium compound 11 and the catalyst 12 prepared in step 210 is added to the DMF solution in which the polymer material is dissolved, and the electrospinning stock solution is formed by sufficient stirring.
[0125] Step 230, electrospinning the electrospinning stock solution to obtain a precursor.
[0126] As an example, a precursor of a composite material is obtained by coaxial electrospinning.
[0127] During the electrospinning process, the polymer in the electrospinning stock solution will spontaneously wrap the lithium-containing compound 11 and the catalyst 12, thereby forming a precursor that completely wraps the lithium-containing compound 11 and the catalyst 12. After calcination, the polymer in the precursor is carbonized, the DMF solution disappears, and a composite material 1 with a hollow tubular structure is formed. In the composite material 1, there may be a certain gap between the lithium-containing compound 11 and the catalyst 12 and the inner wall of the tubular structure of the carbon material 13.
[0128] Step 240 , calcining the precursor in an inert atmosphere to obtain a composite material 1 .
[0129] The precursor is calcined in an inert atmosphere, and the polymer material can be removed through a carbonization process, thereby forming a carbon material 13 with an internal hollow tubular structure. At the same time, the inner wall of the tubular structure of the carbon material 13 is provided with a lithium-containing compound 11 and a catalyst 12.
[0130] Through the above method 200, the composite material 1 of the embodiment of the present application can be prepared, and the composite material 1 is beneficial to improving the capacity of the battery cell.
[0131] In some embodiments, the chemical formula of the lithium-containing compound 11 is Li2C x O y , wherein 1≤x≤4, 3≤y≤6. Optionally, the lithium-containing compound 11 includes at least one of Li2C2O4, Li2CO3, Li2C4O4, Li2C3O5 or Li2C4O6.
[0132] In some embodiments, the transition metal oxide has the formula M α O β , wherein 0<α≤3, 0<β≤5, M includes at least one of Ni, Co, Fe, Mn, V, Cr, Cu or Ti; optionally, M α O β Includes: at least one of NiO, Co3O4, Fe2O3, MoO3 or V2O5.
[0133] In some embodiments, the carbide of the transition metal includes at least one of molybdenum carbide, vanadium carbide, tungsten carbide, titanium carbide, cobalt carbide, iron carbide or nickel carbide; and / or, the nitride of the transition metal includes at least one of molybdenum nitride, vanadium nitride, titanium nitride, manganese nitride, cobalt nitride, iron nitride or nickel nitride.
[0134] In some embodiments, the solute in the slurry containing the polymer material includes the polymer material, and the solvent in the slurry containing the polymer material is an organic solvent; optionally, the organic solvent includes N,N-dimethylformamide. The polymer material has good solubility in the organic solvent, and after adding the polymer powder to the organic solvent, it is easy to prepare the above solution. N,N-dimethylformamide has good stability, so that the above slurry has good performance.
[0135] In some embodiments, the mass ratio D of the polymer material to N,N-dimethylformamide satisfies: 1:20≤D≤1:1.
[0136] D can be 1:20, 1:15, 1:10, 1:8, 1:5, 1:1 or any value within the above range. When D is not less than 1:20, the polymer material and N, N-dimethylformamide have a suitable mass ratio, which is convenient for the smooth progress of electrospinning and can reduce the difficulty of electrospinning; when D does not exceed 1:1, the risk of a thin electrospinning solution caused by more N, N-dimethylformamide and less polymer material can be reduced, thereby reducing the risk of composite material breakage during subsequent calcination. By reasonably setting the size of D, it is convenient for the smooth progress of electrospinning and the preparation of composite material 1, and it is convenient to obtain carbon material 13 with a suitable mass ratio through the subsequent calcination process.
[0137] In some embodiments, D satisfies: 1:10≤D≤1:5.
[0138] In some embodiments, the polymer material includes at least one of polyvinyl pyrrolidone, polyacrylonitrile or polyethylene oxide. As an example, the polymer is polyacrylonitrile.
[0139] In some embodiments, the calcination temperature T satisfies: 300°C≤T≤480°C.
[0140] T may be 300° C., 350° C., 400° C., 450° C., 480° C., or any value within the above range.
[0141] By setting the calcination temperature T to satisfy 300°C≤T≤480°C, it is beneficial to achieve sufficient carbonization of the polymer material and reduce the risk of thermal decomposition of the lithium-containing compound due to excessively high temperature, thereby facilitating the preparation of the carbon material 13 having a hollow tubular structure.
[0142] In some embodiments, T satisfies: 350°C≤T≤450°C.
[0143] In some embodiments, step 210 includes: mixing the lithium-containing compound 11 and the catalyst 12 and performing high-energy ball milling to obtain a mixed material of the lithium-containing compound 11 and the catalyst 12 .
[0144] High-energy ball milling refers to a method of using the rotation or vibration of the ball mill to make the hard balls strongly impact, grind, and stir the raw materials, and crush the powder into nano-sized particles through the shear force between the ball mills.
[0145] As an example, the lithium-containing compound 11 and the catalyst 12 may be ball-milled using a high-energy ball mill.
[0146] Through high-energy ball milling, lithium-containing compounds 11 and catalysts 12 with smaller particle sizes can be obtained, which is beneficial for making the lithium-containing compounds 11 and catalysts 12 mix more evenly, and is beneficial for increasing the specific surface area and activity of the lithium-containing compounds 11 and catalysts 12, thereby helping to improve the catalytic effect of the catalyst 12.
[0147] In some embodiments, the ball-to-material ratio F of the high-energy ball mill satisfies: 10:1≤F≤15:1; and / or, the revolution speed R1 of the high-energy ball mill satisfies 1000r / min≤R1≤1500r / min; and / or, the rotation speed R2 of the high-energy ball mill satisfies: 2500r / min≤R2≤3000r / min. In this way, the high-energy ball mill has suitable process parameters, which is convenient for obtaining lithium-containing compounds 11 and catalysts 12 with suitable particle sizes.
[0148] The ball-to-material ratio refers to the mass ratio of the ball mill to the material in the ball mill, that is, the mass ratio of the ball mill to the lithium-containing compound 11 and the catalyst 12. The revolution speed may refer to the speed of the main wheel of the ball mill; the rotation speed may refer to the speed of the ball mill.
[0149] F can be 10:1, 12:1, 15:1 or any value within the above range, R1 can be 1000r / min, 1200r / min, 1500r / min or any value within the above range, and R2 can be 2500r / min, 2800r / min, 3000r / min or any value within the above range.
[0150] In some embodiments, the mass ratio K of the lithium-containing compound 11 to the catalyst 12 satisfies: 15:1≤K≤40:1. In this way, the lithium-containing compound 11 and the catalyst 12 have a suitable mass ratio, and the lithium-containing compound 11 can be more fully decomposed under the catalytic action of the catalyst 12, which is beneficial to improving the capacity of the battery cell.
[0151] K can be 15:1, 20:1, 30:1, 40:1 or any value within the above range.
[0152] In some embodiments, the average volume particle size Dv of the lithium-containing compound 11 is 1 50 is greater than the average volume particle size Dv of catalyst 12 2 50. Optionally, the average volume particle size Dv of the lithium-containing compound 11 is 1 50 and the average volume particle size Dv of catalyst 12 2 The difference between 50 and 50 is 50nm to 1000nm.
[0153] In some embodiments, the average volume particle size Dv of the lithium-containing compound 11 is 1 50Satisfy: 100nm≤Dv 150≤1000nm, average volume particle size Dv of catalyst 12 2 50 satisfies: 50nm≤Dv 2 50≤500nm.
[0154] In some embodiments, during electrospinning, the voltage is 15 kV, the propulsion speed of the electrospinning stock solution is 0.2 mL / min, the receiving distance is 15 cm, and the spinning time is 12 h. In this way, the preparation of the composite material 1 is facilitated by appropriate preparation process parameters.
[0155] It should be noted that in the embodiments of the present application, other parameters such as voltage, propulsion speed, receiving distance, spinning time, etc. can also be set according to actual needs, and the embodiments of the present application include but are not limited to this.
[0156] [Positive electrode]
[0157] An embodiment of the present application provides a positive electrode plate, comprising a positive electrode active material; and a composite material 1 according to any of the above embodiments, and / or a composite material 1 prepared by a method according to any of the above embodiments.
[0158] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on the positive electrode current collector.
[0159] The positive electrode current collector may be a metal foil or a composite current collector. For example, the positive electrode current collector may be an aluminum foil.
[0160] The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0161] The positive electrode film layer includes a positive electrode active material. The positive electrode active material can be a positive electrode active material for a battery known in the art. For example, the positive electrode active material is lithium iron phosphate, a ternary material, a lithium-rich manganese-based material, and the like.
[0162] The positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0163] The positive electrode film layer may also optionally include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0164] In some embodiments, the resistance R of the positive electrode sheet satisfies: 0.3Ω<R<0.5Ω. In this way, the positive electrode sheet has appropriate conductivity and the battery cell has appropriate capacity.
[0165] [Negative electrode]
[0166] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on the negative electrode current collector.
[0167] The negative electrode current collector may be a metal foil or a composite current collector. The negative electrode current collector may be a copper foil. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0168] The negative electrode film layer includes a negative electrode active material. The negative electrode active material can be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0169] The negative electrode film layer may also optionally include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0170] [Electrolytes]
[0171] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application embodiment has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0172] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0173] The electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorobisoxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0174] The solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0175] The electrolyte may also optionally include negative electrode film-forming additives, positive electrode film-forming additives, and may also include performance additives that can improve certain battery properties, such as improving battery overcharge performance, improving battery high temperature or low temperature performance, etc.
[0176] [Isolation film]
[0177] The separator is used to separate the positive electrode sheet from the negative electrode sheet. The embodiment of the present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.
[0178] The material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0179] The positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly through a winding process or a lamination process.
[0180] [Battery Cell]
[0181] An embodiment of the present application provides a battery cell, comprising the positive electrode plate in the above embodiment.
[0182] The battery cell of the embodiment of the present application may be a battery cell that has not been charged or discharged. For example, the battery cell is a battery cell that has just been assembled and has not been used. For example, the battery cell is a battery cell that has not been subjected to a formation process.
[0183] After the battery cell is assembled and used for a period of time, the lithium-containing compound 11 of the composite material 1 is decomposed in the pole piece in the battery cell, and only a small amount of or no lithium-containing compound 11 exists in the pole piece.
[0184] The embodiment of the present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. The battery cell may be a lithium-ion battery, a lithium-sulfur battery, a sodium-ion battery, a magnesium-ion battery, etc.
[0185] Figure 3 Schematic diagram of a battery cell according to an embodiment of the present application. Figure 3 As shown, the battery cell 3 is a square battery cell and includes a housing 31 , an end cap assembly 32 and an electrode assembly 33 disposed in the housing 31 .
[0186] The electrode assembly 33 may be made of a positive electrode sheet, a negative electrode sheet and a separator through a winding process or a lamination process.
[0187] The end cap assembly 32 includes an electrode terminal 322, such as Figure 3 As shown, the end cap assembly 32 includes two electrode terminals 322, one of which is a positive electrode terminal and the other is a negative electrode terminal.
[0188] The battery cell 3 further includes a current collecting member 34, which is used to connect the electrode tab 331 and the electrode terminal 322 of the electrode assembly 33. For example, when the electrode sheet 1 of the embodiment of the present application is a positive electrode sheet, one current collecting member 34 is used to connect the positive electrode tab (which may also be the electrode tab 102 of the electrode sheet 1) and the positive electrode terminal, and the other current collecting member 34 is used to connect the negative electrode tab and the negative electrode terminal.
[0189] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0190] [Battery]
[0191] An embodiment of the present application provides a battery, comprising the battery cell in the above embodiment. Figure 4 Schematic diagram of a battery according to an embodiment of the present application. Figure 4 As shown, the battery 5 may include a plurality of battery cells (not shown in the figure).
[0192] The battery cells 3 can directly form the battery 5 , or can first form a battery module, and then multiple battery modules form the battery 5 .
[0193] [Electrical devices]
[0194] An embodiment of the present application provides an electrical device, comprising the battery described in the above embodiment.
[0195] Figure 5 FIG. 1 is a schematic diagram of an electrical device according to an embodiment of the present application. Figure 5As shown, the present application provides an electrical device 6, including the battery in the above embodiment.
[0196] Optionally, the electrical device may also be an energy storage device, a lighting device, a spacecraft, etc. The embodiments of the present application include but are not limited to these.
[0197] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0198] [Example]
[0199] Example 1
[0200] In the process of preparing the composite material, the mass ratio K of the lithium-containing compound to the catalyst is 17:1, and the average volume particle size Dv of the lithium-containing compound is 1 50 is 500nm, the average volume particle size Dv of the catalyst 2 50 is 200 nm, the polymer material is polyacrylonitrile, the mass ratio of the polymer material to DMF is 1:10, and the calcination temperature T is 400°C.
[0201] In the prepared composite material, the mass content A of the carbon material is 10wt%, the mass content B of the catalyst is 5wt%, and the mass content C of the lithium-containing compound is 85wt%. The aspect ratio E of the carbon material is 1500:1, the decomposition voltage V1 of the lithium-containing compound is 4.35V, and the powder resistivity P of the composite material is 0.21Ω·cm.
[0202] Embodiment 2-5
[0203] The difference between Example 2-5 and Example 1 is that the mass content A of the carbon material is different.
[0204] The mass content of the carbon material is related to the amount of polymer material added during the preparation process. The more polymer material added, the greater the mass content A of the carbon material. The mass content of the added polymer material can be calculated by the mass content of the carbon material.
[0205] Embodiment 6-9
[0206] The difference between Examples 6-9 and Example 1 is that the mass content B of the catalyst is different.
[0207] Examples 10-13
[0208] The difference between Examples 10-13 and Example 1 is that the aspect ratio E of the carbon material is different.
[0209] Examples 14-17
[0210] The difference between Examples 14-17 and Example 1 is that the mass ratios of the polymer material and DMF are different.
[0211] Examples 18-21
[0212] The difference between Examples 18-21 and Example 1 is that the calcination temperature T is different.
[0213] Examples 22-24
[0214] The difference between Examples 22-24 and Example 1 is that the average volume particle size Dv of the lithium-containing compound is 1 50 and the average volume particle size Dv of the catalyst 2 50 different.
[0215] Examples 25-27
[0216] The difference between Examples 25-27 and Example 1 is that the types of lithium-containing compounds are different.
[0217] Examples 28-29
[0218] The difference between Examples 28-29 and Example 1 is that the types of catalysts are different.
[0219] Embodiment 30
[0220] The difference between Example 30 and Example 1 is that the mass ratio of carbon material and catalyst is lower, and the aspect ratio of carbon material is lower.
[0221] Embodiment 31
[0222] The difference between Example 31 and Example 1 is that the mass proportion of carbon material is higher, and the mass of polymer and DMF is higher.
[0223] Embodiment 32
[0224] The difference between Example 32 and Example 1 is that the mass proportion of the catalyst is higher and the calcination temperature is higher.
[0225] Embodiment 33
[0226] The difference between Example 33 and Example 1 is that the aspect ratio of the carbon material is higher, the mass of the polymer and DMF is lower, and the calcination temperature is lower.
[0227] Examples 34-35
[0228] The difference between Examples 34-35 and Example 1 is that the catalysts are respectively carbides of transition metals and nitrides of transition metals.
[0229] Embodiment 36
[0230] The difference between Example 36 and Example 1 is that during the preparation of the positive electrode plate, lithium iron phosphate (LFP) is added as the positive electrode active material.
[0231] Comparative Example 1
[0232] The difference between Comparative Example 1 and Example 1 is that its material is not a composite material but only a lithium-containing compound.
[0233] Comparative Example 2
[0234] The difference between Comparative Example 2 and Example 1 is that its material is a mixture of a lithium-containing compound and a catalyst.
[0235] Comparative Example 3
[0236] The difference between Comparative Example 3 and Example 1 is that its material is a carbon-coated lithium-containing compound.
[0237] Comparative Example 4
[0238] The difference between Comparative Example 4 and Example 25 is that its material is not a composite material, but only a lithium-containing compound.
[0239] Comparative Example 5
[0240] The difference between Comparative Example 5 and Example 26 is that its material is not a composite material, but only a lithium-containing compound.
[0241] Comparative Example 6
[0242] The difference between Comparative Example 6 and Example 27 is that its material is not a composite material, but only a lithium-containing compound.
[0243] Comparative Example 7
[0244] The difference between Comparative Example 7 and Example 36 is that the added material is not a composite material, but only a lithium-containing compound.
[0245] Comparative Example 8
[0246] The difference between Comparative Example 8 and Example 36 is that the added material is a mixture of a lithium-containing compound and a catalyst.
[0247] Comparative Example 9
[0248] The difference between Comparative Example 9 and Example 36 is that the added material is a carbon-coated lithium-containing compound.
[0249] As shown in Table 1 and Table 2, in Examples 1-34 and Comparative Examples 1-6, lithium-ion battery monomers were prepared using the composite material as the positive electrode active material.
[0250] In Tables 1 and 3, A is the mass content of the carbon material, B is the mass content of the catalyst, C is the mass content of the lithium-containing compound, K is the mass ratio of the lithium-containing compound to the catalyst, and D is the mass ratio of the lithium-containing compound to the catalyst. v 1 50 is the average volume particle size of the lithium-containing compound, D v 2 50 is the average volume particle size of the catalyst, E is the mass ratio of the carbon material, D is the mass ratio of the polymer material to DMF, and T is the calcination temperature. In Tables 2 and 3, V1 is the decomposition voltage of the lithium-containing compound, P is the powder resistivity of the composite material, Q is the first cycle charging capacity of the battery cell, and R is the membrane resistance after the electrode is fully charged.
[0251] Table 1 Parameters of Examples and Comparative Examples
[0252]
[0253]
[0254] Table 2 Experimental results of comparative examples and embodiments
[0255]
[0256]
[0257] [Preparation of battery cells]
[0258] (1) Preparation of positive electrode sheet: The composite material, binder polyvinylidene fluoride (PVDF), and conductive agent (acetylene black) are dissolved in solvent N-methylpyrrolidone (NMP) at a mass ratio of 97:2:1, and the mixture is stirred and mixed to prepare positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then dried, cold pressed, and cut to obtain positive electrode sheet. In the preparation of the positive electrode sheet, the composite material is used as the active material, and no other active materials are added.
[0259] (2) Preparation of negative electrode sheets: artificial graphite, a negative electrode active material, acetylene black, a conductive agent, styrene butadiene rubber (SBR), a binder, and sodium carboxymethyl cellulose (CMC-Na), a thickener, are dissolved in deionized water at a mass ratio of 96:1.5:1.5:1.0, and the mixture is stirred thoroughly to prepare a negative electrode slurry; the negative electrode slurry is coated on a negative electrode current collector copper foil, and then dried, cold pressed, and cut to obtain a negative electrode sheet.
[0260] (3) Isolation film: Polypropylene film is used.
[0261] (4) Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed at a volume ratio of 1:1:1, and then LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte. The concentration of LiPF6 in the electrolyte was 1 mol / L.
[0262] (5) Preparation of lithium-ion batteries: stack and wind the above-mentioned positive electrode sheets, separators, and negative electrode sheets in order to obtain an electrode assembly; place the electrode assembly in an outer package, add the above-prepared electrolyte, and obtain a lithium-ion battery after packaging, standing, forming, aging and other processes.
[0263] As shown in Table 3, in Example 36 and Comparative Examples 7-9, a lithium-ion battery monomer was prepared using the composite material as a lithium supplement and lithium iron phosphate as a positive electrode active material.
[0264] Table 3 Experimental parameters and results of Example 36 and Comparative Examples 7-9
[0265]
[0266] [Preparation of battery cells]
[0267] (1) Preparation of positive electrode sheet: The composite material, positive electrode active material lithium iron phosphate (LFP), binder polyvinylidene fluoride (PVDF), and conductive agent (acetylene black) are dissolved in solvent N-methylpyrrolidone (NMP) at a mass ratio of 95:2:2:1, and the mixture is stirred and mixed to prepare positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then dried, cold pressed, and cut to obtain a positive electrode sheet. In the preparation of the positive electrode sheet, the composite material is used as a lithium supplement.
[0268] (2) Preparation of negative electrode sheets: artificial graphite, a negative electrode active material, acetylene black, a conductive agent, styrene butadiene rubber (SBR), a binder, and sodium carboxymethyl cellulose (CMC-Na), a thickener, are dissolved in deionized water at a mass ratio of 96:1.5:1.5:1.0, and the mixture is stirred thoroughly to prepare a negative electrode slurry; the negative electrode slurry is coated on a negative electrode current collector copper foil, and then dried, cold pressed, and cut to obtain a negative electrode sheet.
[0269] (3) Isolation film: Polypropylene film is used.
[0270] (4) Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed at a volume ratio of 1:1:1, and then LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte. The concentration of LiPF6 in the electrolyte was 1 mol / L.
[0271] (5) Preparation of lithium-ion batteries: stack and wind the above-mentioned positive electrode sheets, separators, and negative electrode sheets in order to obtain an electrode assembly; place the electrode assembly in an outer package, add the above-prepared electrolyte, and obtain a lithium-ion battery after packaging, standing, forming, aging and other processes.
[0272] [Testing the first cycle charging capacity of lithium-ion batteries]
[0273] The assembled lithium-ion battery was charged at a constant current of 0.1C to 4.25V, left to stand for 5 minutes, and the first-cycle charging capacity of the lithium-ion battery was recorded. The first-cycle charging capacity of the lithium-ion battery was obtained by dividing the first-cycle charging capacity of the battery by the mass of the composite material.
[0274] [Testing of the average volume particle size of catalysts and lithium-containing compounds]
[0275] The average volume particle size can be determined by a particle size analyzer-laser diffraction method. Specifically, the standard GB / T19077-2016 can be referred to, and a laser diffraction scattering particle size analyzer can be used to measure according to the manufacturer's instructions. For example, before preparing the composite material, appropriate amounts of the catalyst and the lithium-containing compound are taken respectively, and the average volume particle size of the material is tested using a Malvern 2000 (MasterSizer 2000) laser particle size analyzer. For example, take an appropriate amount of the sample to be tested (the sample concentration is sufficient to ensure 8-12% shading), add 20 ml of deionized water, and at the same time, supercharge for 5 minutes (53KHz / 120W) to ensure that the sample is completely dispersed, and then measure the sample according to the GB / T19077-2016 / ISO 13320:2009 standard.
[0276] [Testing of powder resistivity of composite materials]
[0277] The powder of the composite material was dried, and an appropriate amount of powder was weighed. Then, a powder resistivity tester (ST2722 digital four-probe tester, manufactured by Suzhou Jingge Electronics Co., Ltd.) was used to measure the powder resistivity of the sample according to GB / T 30835-2014, and the test pressure was 20 MPa.
[0278] [Test of aspect ratio]
[0279] The aspect ratio of the carbon material is the same as that of the composite material, which can be measured by transmission electron microscopy. Normally, 20 well-dispersed composite materials are taken, their outer diameters and lengths are tested respectively, and the average value is taken as the aspect ratio of the carbon material.
[0280] [Decomposition voltage test]
[0281] The decomposition voltage of the lithium-containing compound is the average charging voltage during the first charging process, that is, the ratio of charging energy / charging capacity.
[0282] [Test of the resistance of the electrode]
[0283] After fully charging the positive electrode, disassemble it and select the cutting area of 1540mm on the left, middle and right of the electrode. 2 Turn on the indicator light of the electrode resistor (for example, Yuanneng Technology's electrode resistor), place the small disc in the appropriate position of the "probe" of the membrane resistor, click the "start" button, wait for the reading to stabilize, and then read it. Each small disc tests two positions, and finally calculates the average value of six measurements, which is the membrane resistance of the electrode.
[0284] [Testing of the mass content of carbon materials, catalysts and lithium-containing compounds in composite materials]
[0285] The components of the composite material and the mass content of each component can be measured in the following way.
[0286] As an example, taking a proper amount of composite material powder and observing it with a scanning electron microscope, a carbon material with a tubular structure can be observed. Secondly, the elemental composition of the composite material can be determined by an energy spectrometer, and then the material and mass content of each component can be determined by thermogravimetric analysis.
[0287] As an example, take an appropriate amount of composite material powder and dissolve the powder in deionized water (or a corresponding soluble solvent). Since the lithium-containing compound can be dissolved in water, the lithium-containing compound can be separated from the composite material, the weight of the lithium-containing compound can be measured, and then the mass content of the lithium-containing compound can be calculated. Afterwards, the undissolved substance in the powder is added to another solvent that can dissolve the catalyst, the weight of the catalyst is measured and the mass content of the catalyst is calculated. Finally, a substance containing only carbon material can be obtained, so that the mass content of the carbon material can be obtained by weighing.
[0288] It should be noted that the first-cycle charging capacity, average volume particle size, resistivity, aspect ratio, decomposition voltage, resistance, mass content of carbon material in the composite material, mass content of the catalyst, and mass content of the lithium-containing compound in the embodiments of the present application are common knowledge in the art, have meanings known in the art, and can be measured by testing methods and instruments known in the art.
[0289] As shown in combination with Examples 1-24 and Comparative Example 1, and as shown in combination with Examples 25-27 and Comparative Examples 4-6, compared with adding only lithium-containing compounds, the composite materials of the embodiments of the present application can increase the capacity of the battery cell.
[0290] In combination with Examples 1-5, when the mass content of the carbon material is set to 1wt% to 40wt%, the battery cell has a higher capacity; when the mass content of the carbon material is set to 2wt% to 25wt%, the composite material has a lower powder resistivity and the battery cell has a higher capacity.
[0291] As shown in Examples 6-9, when the mass content of the catalyst is set to 0.1wt% to 20wt%, the battery cell has a higher capacity; when the mass content of the catalyst is set to 0.5wt% to 10wt%, the lithium-containing compound has a lower decomposition voltage and the battery cell has a higher capacity.
[0292] As shown in Examples 10-13, when the aspect ratio of the carbon material is set to 100:1 to 3000:1, the battery cell has a higher capacity; when the aspect ratio of the carbon material is set to 200:1 to 2000:1, the risk of agglomeration of the carbon material is reduced, and the battery cell has a higher capacity.
[0293] As shown in Examples 14-17, when the mass ratio of polymer to DMF is set to 1:1-1:20, the battery monomer has a higher capacity; when the mass ratio of polymer to DMF is set to 1:2-1:15, the battery monomer has an even higher capacity.
[0294] As shown in Examples 18-21, when the calcination temperature is set at 300°C to 480°C, the battery cell has a higher capacity; when the calcination temperature is set at 350°C to 450°C, the carbonization effect of the polymer material is better, and a carbon material with better crystallinity can be obtained. At the same time, the decomposition of lithium-containing compounds at high temperatures can be avoided, and the battery cell has a higher capacity.
[0295] As shown in Examples 22-24, the catalyst and the lithium-containing compound have a smaller particle size, which is beneficial to improving the catalytic effect of the catalyst and reducing the decomposition voltage of the lithium-containing compound; when the particle size of the catalyst and the lithium-containing compound is larger, the catalytic effect of the catalyst is weakened, the decomposition voltage of the lithium-containing compound decreases less, and the capacity of the battery cell is increased less.
[0296] As shown in Examples 25-27, the embodiments of the present application are applicable to a variety of different lithium-containing compounds; as shown in Examples 28-29 and Examples 34-35, the embodiments of the present application are applicable to a variety of different catalysts.
[0297] As shown in Example 30, the mass content of the carbon material is low, and the composite material has a high powder resistivity; the mass content of the catalyst is low, and the decomposition voltage of the lithium-containing compound is high; the aspect ratio of the carbon material is relatively small, and the improvement of the capacity of the battery cell is not obvious. In summary, the battery cell of this embodiment has a low capacity. As shown in Example 31, although the carbon material has a high mass ratio, the mass ratio of the polymer to DMF is relatively large, and the content of DMF is relatively small, it is difficult to obtain a composite material with a good tubular structure by electrospinning, and the composite effect of the lithium-containing compound and the carbon material is poor. The resistivity of the obtained composite material is large, and the battery cell has a low capacity. As shown in Example 32, the mass content of the catalyst is large, so the mass content of the lithium-containing compound is low; in addition, the calcination temperature is high, and part of the carbon material and the lithium-containing compound undergo thermal decomposition, causing the tubular structure to be destroyed, the resistivity of the composite material increases, and the battery cell has a low capacity; as shown in Example 33, the aspect ratio of the carbon material is relatively large, and the carbon material agglomerates, resulting in an increase in the resistivity of the powder of the composite material, and the battery cell has a low capacity.
[0298] As shown in Comparative Example 2, only the lithium-containing compound and the catalyst are mixed. The mixed material has a high resistivity and cannot solve the adverse effects of vacancies caused by the decomposition of the lithium-containing compound. The capacity of the battery cell is low.
[0299] As shown in Comparative Example 3, only the method of carbon coating lithium-containing compounds is used, and the decomposition voltage of the lithium-containing compounds is relatively high, which is not conducive to increasing the capacity of the battery cell. Although in Comparative Example 3, only the method of carbon coating lithium-containing compounds is used, the resistivity of the powder and the resistance of the membrane are relatively low, but due to the high decomposition voltage of the lithium-containing compounds, it is difficult to use normally.
[0300] As shown in Example 36 and Comparative Examples 7-9, after the composite material of the embodiment of the present application is mixed with the positive electrode active material lithium iron phosphate, the battery monomer prepared has a higher capacity.
[0301] Although only lithium iron phosphate is shown as the positive electrode active material in the embodiment, the composite material of the present application is also applicable to battery cells of other active materials. Similarly, although only the embodiment of transition metal oxides as catalysts is shown, other catalysts that can be used to catalyze the decomposition of lithium-containing compounds, such as transition metal carbides, transition metal nitrides, etc., can also be applied to the embodiments of the present application.
[0302] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A composite material, characterized in that: include: Containing lithium compounds, catalysts and carbon materials, in, The carbon material has a hollow tubular structure, and the lithium-containing compound and the catalyst are disposed in the tubular structure; The lithium-containing compound comprises lithium, carbon and oxygen; The catalyst includes at least one of a transition metal oxide, a transition metal carbide, or a transition metal nitride.
2. The composite material according to claim 1, characterized in that The lithium-containing compound and the catalyst are arranged on the inner wall of the tubular structure.
3. The composite material according to claim 1 or 2, characterized in that: At least a portion of the catalyst is located on the surface of the lithium-containing compound.
4. The composite material according to any one of claims 1 to 3, characterized in that The chemical formula of the lithium-containing compound is Li2C x O y , wherein 1≤x≤4, 3≤y≤6; optionally, the lithium-containing compound includes at least one of Li2C2O4, Li2CO3, Li2C4O4, Li2C3O5 or Li2C4O6.
5. The composite material according to any one of claims 1 to 4, characterized in that The chemical formula of the transition metal oxide is M α O β , wherein 0<α≤3, 0<β≤5, and M includes at least one of Ni, Co, Fe, Mn, V, Cr, Cu or Ti; Optionally, M α O β Includes: at least one of NiO, Co3O4, Fe2O3, MoO3 or V2O5.
6. The composite material according to any one of claims 1 to 5, characterized in that The carbide of the transition metal includes: at least one of molybdenum carbide, vanadium carbide, tungsten carbide, titanium carbide, cobalt carbide, iron carbide or nickel carbide; and / or, the nitride of the transition metal includes: at least one of molybdenum nitride, vanadium nitride, titanium nitride, manganese nitride, cobalt nitride, iron nitride or nickel nitride.
7. The composite material according to any one of claims 1 to 6, characterized in that Based on the total mass of the composite material, the mass content A of the carbon material satisfies: 1wt%≤A≤40wt%; optionally, A satisfies: 2wt%≤A≤25wt%.
8. The composite material according to any one of claims 1 to 7, characterized in that Based on the total mass of the composite material, the mass content B of the catalyst satisfies: 0.1wt%≤B≤20wt%; optionally, B satisfies: 0.5wt%≤B≤10wt%.
9. The composite material according to any one of claims 1 to 8, characterized in that Based on the total mass of the composite material, the mass content C of the lithium-containing compound satisfies: 45wt%≤B≤98.9wt%; optionally, C satisfies: 70wt%≤B≤85wt%.
10. The composite material according to any one of claims 1 to 9, characterized in that The aspect ratio E of the carbon material satisfies: 100:1≤E≤3000:1; optionally, E satisfies: 200:1≤E≤2000:
1.
11. The composite material according to any one of claims 1 to 10, characterized in that In the composite material, the decomposition voltage V1 of the lithium-containing compound satisfies: V1<4.8V; Optionally, V1 satisfies: V1<4.4V.
12. The composite material according to any one of claims 1 to 11, characterized in that The resistivity P of the composite material satisfies: 0.2Ω·cm<P<101Ω·cm; optionally, P satisfies: 0.2Ω·cm<P<5.5Ω·cm.
13. The composite material according to any one of claims 1 to 12, characterized in that The average volume particle size Dv of the lithium-containing compound 1 50 is greater than the average volume particle size Dv of the catalyst 2 50; Optionally, the average volume particle size Dv of the lithium-containing compound 1 50Satisfy: 100nm≤Dv 1 50≤1000nm, the average volume particle size Dv of the catalyst 2 50 satisfies: 50nm≤Dv 2 50≤500nm.
14. A method for preparing the composite material according to any one of claims 1 to 13, characterized in that: include: Mixing a lithium-containing compound and a catalyst to obtain a mixed material of the lithium-containing compound and the catalyst, wherein the catalyst comprises at least one of an oxide of a transition metal, a carbide of a transition metal, or a nitride of a transition metal, and the lithium-containing compound comprises lithium, carbon, and oxygen; Adding the mixed material of the lithium-containing compound and the catalyst into a slurry containing a polymer material to obtain an electrospinning stock solution; Electrospinning the electrospinning stock solution to obtain a precursor; The precursor is calcined in an inert atmosphere to obtain the composite material.
15. The method according to claim 14, characterized in that The chemical formula of the lithium-containing compound is Li2C x O y , wherein 1≤x≤4, 3≤y≤6; optionally, the lithium-containing compound includes at least one of Li2C2O4, Li2CO3, Li2C4O4, Li2C3O5 or Li2C4O6.
16. The method according to claim 14 or 15, characterized in that The chemical formula of the transition metal oxide is M α O β , wherein 0<α≤3, 0<β≤5, M includes at least one of Ni, Co, Fe, Mn, V, Cr, Cu or Ti; optionally, M α O β Includes: at least one of NiO, Co3O4, Fe2O3, MoO3 or V2O5.
17. The method according to any one of claims 14 to 16, characterized in that: The carbide of the transition metal includes: at least one of molybdenum carbide, vanadium carbide, tungsten carbide, titanium carbide, cobalt carbide, iron carbide or nickel carbide; and / or, the nitride of the transition metal includes: at least one of molybdenum nitride, vanadium nitride, titanium nitride, manganese nitride, cobalt nitride, iron nitride or nickel nitride.
18. The method according to any one of claims 14 to 17, characterized in that: The solute in the slurry containing the polymer material includes the polymer material, and the solvent in the slurry containing the polymer material is an organic solvent; optionally, the organic solvent includes N,N-dimethylformamide.
19. The method according to any one of claims 14 to 18, characterized in that The polymer material includes: at least one of polyvinyl pyrrolidone, polyacrylonitrile or polyethylene oxide; optionally, the polymer material includes polyacrylonitrile.
20. The method according to claim 18 or 19, characterized in that The mass ratio D of the polymer material to the N,N-dimethylformamide satisfies: 1:20≤D≤1:1; optionally, D satisfies: 1:15≤D≤1:
2.
21. The method according to any one of claims 14 to 20, characterized in that The calcination temperature T satisfies: 300°C≤T≤480°C; optionally, T satisfies: 350°C≤T≤450°C.
22. The method according to any one of claims 14 to 21, characterized in that The method of mixing the lithium-containing compound and the catalyst to obtain a mixed material of the lithium-containing compound and the catalyst comprises: The lithium-containing compound and the catalyst are mixed and subjected to high-energy ball milling to obtain a mixed material of the lithium-containing compound and the catalyst.
23. The method according to claim 22, characterized in that The ball-to-material ratio F of the high-energy ball mill satisfies: 10:1≤F≤15:1; and / or, the revolution speed R1 of the high-energy ball mill satisfies: 1000r / min≤R1≤1500r / min; and / or, the rotation speed R2 of the high-energy ball mill satisfies: 2500r / min≤R2≤3000r / min.
24. The method according to any one of claims 14 to 23, characterized in that The mass ratio C of the lithium-containing compound to the catalyst satisfies: 15:1≤C≤40:
1.
25. The method according to any one of claims 14 to 24, characterized in that The average volume particle size Dv of the lithium-containing compound 1 50 is greater than the average volume particle size Dv of the catalyst 2 50; Optionally, the average volume particle size Dv of the lithium-containing compound 1 50Satisfy: 100nm≤Dv 1 50≤1000nm, the average volume particle size Dv of the catalyst 2 50 satisfies: 50nm≤Dv 2 50≤500nm.
26. A positive electrode plate, characterized in that: include: Positive electrode active material; The composite material according to any one of claims 1 to 13, and / or, a composite material prepared by the method according to any one of claims 14 to 25.
27. The positive electrode sheet according to claim 26, characterized in that: The resistance R of the positive electrode plate satisfies: 0.3Ω<R<0.5Ω.
28. A battery cell, characterized in that: Comprising the positive electrode sheet as described in claim 26 or 27.
29. A battery, characterized in that: Comprising the battery cell as claimed in claim 28.
30. An electrical device, characterized in that: Comprising a battery as claimed in claim 29.
Citation Information
Patent Citations
Micro-nano-structure anode material for Li-air battery and preparation method of micro-nano-structure anode material
CN102637879A
Nanometer composite material and preparation method thereof, positive electrode material and battery
CN103137976A
Preparation method of lithium iron phosphate / carbon nanotube composite positive electrode material
CN111740113A
Multifunctional current collector and preparation method and application thereof
CN114551900A
Positive electrode lithium-supplementing agent, preparation method therefor and use thereof
WO2022105259A1